ANALYSIS OF EFFECT OF ACQUISITIONS ON FINANCIAL PERFORMANCE OF ACQUIRER COMPANIES AND ACQUIRED COMPANIES (Case Study of Companies Listed on the Indonesia Stock Exchange Year 2008-2010) - Wikasari, Ika; Affandy, Didied Poernawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine how the effect of the acquisition on the financial performance of the acquirer and the acquired company after the acquisition done. The population in this study are all public companies listed on the Indonesia Stock Exchange during the years 2008 to 2010. The sample in this study consisted of 8 the acquirer companies and 5 the acquired companies. The financial performance of the company in this study was measured using financial ratios consist of liquidity ratios, activity ratios, leverage ratios and profitability ratios. Tests performed using Paired Samples T test. The results of the analysis of financial ratios on the acquirer and the acquired company indicates that there was no significant difference between the two years before and one year before to one year after the acquisition. From these results we can conclude that the acquisition does not generally have a significant influence on the financial performance of the acquirer and the acquired company are proxied by financial ratios. This was probably due to lack of strategy and lack of experience in acquisition activity. Keywords: acquisition, the company's performance, financial ratios